2016
DOI: 10.1016/j.hpb.2016.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Liver function declines with increased age

Abstract: This study shows that liver function deteriorates with age. Since the regenerative capacity of the liver correlates with liver function, this finding should be taken into account when assessing surgical risk in patients considered for major liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
60
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 26 publications
(29 reference statements)
1
60
0
Order By: Relevance
“…Such studies confirmed that like chromosomal alterations also base substitution mutations accumulate with age in human brain (8,9), intestine and liver (4).Due to its high metabolic and detoxification activity liver is more likely to be adversely affected by various damaging agents than most other organs. In humans this may cause agerelated loss of function, most notably a severe reduction in metabolic capacity and multiple pathologies, including fatty liver disease, cirrhosis, hepatitis, infections and cancer (10,11). To test if somatic mutations occur with a high frequency and accumulate rapidly with age we performed WGS on single primary hepatocytes from human donors varying in age between 5 months and 77 years of age.…”
mentioning
confidence: 99%
“…Such studies confirmed that like chromosomal alterations also base substitution mutations accumulate with age in human brain (8,9), intestine and liver (4).Due to its high metabolic and detoxification activity liver is more likely to be adversely affected by various damaging agents than most other organs. In humans this may cause agerelated loss of function, most notably a severe reduction in metabolic capacity and multiple pathologies, including fatty liver disease, cirrhosis, hepatitis, infections and cancer (10,11). To test if somatic mutations occur with a high frequency and accumulate rapidly with age we performed WGS on single primary hepatocytes from human donors varying in age between 5 months and 77 years of age.…”
mentioning
confidence: 99%
“…Apart from the influence of life expectancy, elderly patients with HCC are generally characterized by age-related deterioration of liver function and higher incidences of comorbidities, which are related to higher perioperative risk. [ 8 31 ] Considering these characteristics, the advantages of RFA over SR, such as minimal invasiveness, less blood loss, lower perioperative risk, and fewer deteriorative effects on liver function, must not be overlooked. [ 13 24 32 ] In addition, tumor diameter ≤3 cm is deemed as a favorable prognostic factor for both OS and LCSS, and several studies have proved that RFA can provide comparable survival rates to SR for selected patients with HCC with single tumors ≤3 cm in diameter, if a patient's performance status, tumor location, and underlying liver function are considered.…”
Section: Discussionmentioning
confidence: 99%
“…However, as a unique group, elderly patients with HCC are generally characterized by age-related deterioration of liver function and higher incidences of comorbidities. [ 8 ] Therefore, RFA has been established as the most common alternative treatment for elderly patients with small HCC because of its excellent antitumor effect and its advantage of less invasiveness, lower perioperative risk, and fewer deteriorative effects on liver function than SR.[ 9 ] Nevertheless, RFA has a significant drawback of limited ablative margins, which is associated with high risk of marginal recurrence. [ 10 ] With advancement of surgical techniques and perioperative management, feasibility, safety, and effectiveness of SR for selected elderly patients with early-stage HCC have been widely identified in the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al [ 27 ] found that the mortality of HBV related liver failure increased markedly with increasing age ≥ 35 years in males and ≥ 55 years in females. In patients with chronic liver disease, liver function deteriorates with age and the regenerative capacity of the liver declines [ 28 ]. The older patients are more easily combined with complications because of low immunity.…”
Section: Discussionmentioning
confidence: 99%